USE OF LOCAL RESOURCES IN COOKING AND PMT DEMONSTRATION ACTIVITIES FOR STUNTING PREVENTION IN PANJI SARI DISTRICT (Jurnal Wicara Desa, 2024)
The Community Real Work Program (KKN PMD) is an educational program that provides students with direct experience in identifying and overcoming community problems by practicing the knowledge they have gained on campus. In this program, Mataram University students implemented the "Utilization of Local Resources to Prevent Stunting" project in Panji Sari Village, Central Lombok. Stunting is a major health problem in Panji Sari, with a high prevalence of 30.8% among children under five years old. This program aims to reduce stunting through outreach and providing nutritious food or PMT by utilizing local resources, especially tilapia from village dams. This program is implemented by conducting cooking demonstrations and providing additional food (PMT) for pregnant women and children with stunting. The cooking demonstration taught participants how to cook nutritious food using tilapia, as well as providing them with PMT/healthy food packages. The PMD KKN program is implemented in Panji Sari Village, Central Lombok, to tackle stunting through education and providing PMT by utilizing local resources. This program includes cooking demonstrations and providing additional food (PMT) for pregnant women and children diagnosed with stunting. A total of 35 participants took part in a cooking demonstration and received PMT packages. Participants were actively involved in the cooking process and appreciated the simplicity and affordability of the recipe and were active in asking questions and answers about healthy food to overcome stunting. This PMT package contains around 223.1 kcal of protein, 9.8 g of fat and 8.9 g of carbohydrates. This program shows the optimal use of local resources in Panji Sari in overcoming the problem of stunting and promoting healthy eating habits in the community.
Keywords: local resources; dam fish; cooking demonstration; PMT; stunting